Evaluation of Microleakage in Flash-Free and Conventional Ceramic Brackets: A Microcomputed Tomography Study - Gökay Üstdal; Eyüp Burak Küçük (Turkish Journal of Orthodontics)
Objective: The aim of this study was to evaluate and compare microleakage under the conventional and flash-free ceramic brackets bonded with different agents. Methods: Forty extracted human maxillary premolar teeth were randomly divided into five groups. According to the groups, adhesive coated and conventional bracket systems were bonded to the tooth surfaces with the specified adhesive agents. To simulate a six-month oral environment, all teeth were subjected to a thermal cycle procedure. Micro-computed tomography (micro-CT) was used to view and measure the microleakage. Kruskal-Wallis test was used to compare the parameters and Mann-Whitney U test was used for the determination of the group that caused the difference. For intragroup comparisons Wilcoxon signed-rank test was used. Results: Microleakage volume (mm3) and microleakage percentage (%) measured in Blugloo™ group was found significantly lower (p<0.05) then other groups. There was no significant difference in microleakage volume (mm3) and percentage (%) in comparison of gingival and occlusal regions (p>0.05). Conclusion: Adhesive precoated flash-free brackets were not shown a significant difference compared to their conventional equivalent for microleakage volume. The brackets bonded with Blugloo™ adhesive were showed significant less microleakage than the other groups.